2021
DOI: 10.1038/s43705-021-00025-z
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-dependent competition and cooperation relationships between Geobacter and Dehalococcoides for their organohalide respiration

Abstract: Obligate and non-obligate organohalide-respiring bacteria (OHRB) play central roles in the geochemical cycling and environmental bioremediation of organohalides. Their coexistence and interactions may provide functional redundancy and community stability to assure organohalide respiration efficiency but, at the same time, complicate isolation and characterization of specific OHRB. Here, we employed a growth rate/yield tradeoff strategy to enrich and isolate a rare non-obligate tetrachloroethene (PCE)-respiring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…As shown in Figure , the highest 16S rRNA gene sequence similarities of 98.9–99.0% exist with the tetrachloroethene (PCE)-dechlorinating species G. lovleyi, , which presumably also accommodates the 1,2-DCA-dechlorinating Geobacter sp. strain AY…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure , the highest 16S rRNA gene sequence similarities of 98.9–99.0% exist with the tetrachloroethene (PCE)-dechlorinating species G. lovleyi, , which presumably also accommodates the 1,2-DCA-dechlorinating Geobacter sp. strain AY…”
Section: Resultsmentioning
confidence: 99%
“…To date, the capability to utilize chlorinated electron acceptors has been well characterized in G. lovleyi strains. , G. lovleyi strain SZ and the recently isolated strain LYY reduce PCE and trichloroethene (TCE) to cis -1,2-dichloroethene ( c DCE) via hydrogenolysis. , G.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Geobacter lovleyi strain SZ can fulfill the cobamide requirement of Dehalococcoides strains (Yan et al, 2012). Geobacter can also supply carbon source to Dehalococcoides strains by fermenting lactate to acetate (Liang et al, 2021). Also worth mentioning is that, without dynamic monitoring, the abundance and function of Geobacter may be underestimated since community structures were only analyzed at the completion of reductive dechlorination.…”
Section: Discussionmentioning
confidence: 99%
“…Geobacter and Dehalococcoides were the dominant OHRB genera in the second transferred enrichment cultures with relative abundances of 11.12% and 3.42%, respectively. Geobacter lovleyi strain SZ, isolated from Su-Zi Creek sediment of Korea in 2005, and Geobacter lovleyi strain LYY, isolated from black-odorous urban river sediment of China, are capable of PCE-to-cDCE dechlorination (Sung et al, 2006;Amos et al, 2007;Liang et al, 2021). This information suggested that the Geobacter population in the PCEdechlorinating enrichment was responsible for the reductive dechlorination of PCE to cDCE, which was futher dechlorinated to ethene by Dehalococcoides.…”
Section: Microbial Dechlorination Of Pce and 12-dca And Microbial Com...mentioning
confidence: 99%